OMC-1 dust polarization in ALMA Band 7: diagnosing grain alignment mechanisms in the vicinity of Orion Source I. Issue 3 (4th March 2021) - Pattle, Kate; Lai, Shih-Ping; Wright, Melvyn; Coudé, Simon; Plambeck, Richard; Hoang, Thiem; Tang, Ya-Wen; Bastien, Pierre; Eswaraiah, Chakali; Furuya, Ray S; Hwang, Jihye; Inutsuka, Shu-ichiro; et al.
ABSTRACT: We present ALMA Band 7 polarization observations of the OMC-1 region of the Orion molecular cloud. We find that the polarization pattern observed in the region is likely to have been significantly altered by the radiation field of the >10 4 L⊙ high-mass protostar Orion Source I. In the protostar's optically thick disc, polarization is likely to arise from dust self-scattering. In material to the south of Source I – previously identified as a region of 'anomalous' polarization emission – we observe a polarization geometry concentric around Source I. We demonstrate that Source I's extreme luminosity may be sufficient to make the radiative precession time-scale shorter than the Larmor time-scale for moderately large grains ($\gt 0.005\!-\!0.1\, μ$ m), causing them to precess around the radiation anisotropy vector (k-RATs) rather than the magnetic field direction (B-RATs). This requires relatively unobscured emission from Source I, supporting the hypothesis that emission in this region arises from the cavity wall of the Source I outflow. This is one of the first times that evidence for k-RAT alignment has been found outside of a protostellar disc or AGB star envelope. Alternatively, the grains may remain aligned by B-RATs and trace gas infall on to the Main Ridge. Elsewhere, we largely find the magnetic field geometry to be radial around the BN/KL explosion centre, consistent with previous observations. However, in the Main Ridge, the magnetic field geometry appears to remain consistent with the larger-scale magnetic field, perhaps indicative of the ability of the dense Ridge to resist disruption by the BN/KL explosion.